The effects of overoxidation on the morphological and electrical properties of polyaniline (PANI) based solid polymer electrolyte (SPE) - Maliaman, Nur Najiha; Shafiee, Saiful 'Arifin; Mohd Halizan, Muhammad Zharfan; Hassim, Awatif; Shaffee, Siti Nur Amira; Aizamddin, Muhammad Faiz; Kasri, Mohamad Arif; Mahat, Mohd Muzamir (Universiti Putra Malaysia, 2025)
Overoxidation in lithium-ion batteries (LIBs) can occur when a solid polymer electrolyte (SPE) undergoes extreme oxidation, forming undesirable functional groups like carbonyl and hydroxyl. This work examines the effects of overoxidation on polyaniline (PANI)-based SPEs, focusing on morphological, electrical, and structural changes. SPE films composed of PANI, polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were prepared with varying PANI concentrations (1 wt.%, 3 wt.%, and 5 wt.%) and subjected to overoxidation via cyclic voltammetry (CV). Fourier-transform infrared spectroscopy (FTIR) was used to characterize the structural changes, while electrochemical impedance spectroscopy (EIS) assessed electrical conductivity. The highest initial conductivity (1.8×10-5 S/cm) was observed in the composite with 1 wt.% PANI, decreasing to 1.79×10-6 S/cm after overoxidation. Composites with 3 wt.% and 5 wt.%. PANI exhibited lower initial conductivities of 1.41×10-6 S/cm and 1.25×10-6 S/cm, respectively, which further dropped to 4.17×10-7 S/cm and 1.79×10-7 S/cm post-overoxidation. Field-emission scanning electron microscopy (FESEM) revealed that the interpenetrating polymer network (IPN) structures present before treatment were disrupted after overoxidation. FTIR confirmed the formation of hydroxyl and carbonyl species, which correlate with reduced conductivity and degradation of the SPE material. These findings illustrate the detrimental effects of overoxidation on PANI-based SPEs, impacting their structural integrity, morphology, and electrical performance. This has significant implications for LIB efficiency and highlights the importance of mitigating overoxidation in SPEs